Use of ginger to control nausea and vomiting caused by chemotherapy in patients with cervical cancer undergoing treatment - Romeika Lorena Mendes da Silva, BSc; Tâmara Taynah Medeiros da Silva, MD; Renata Lima Pessoa, MD; Ayane Cristine Alves Sarmento, MD; Kleyton Santos Medeiros, PhD; Daniele Vieira Dantas, PhD; Rodrigo Assis Neves Dantas, PhD (Medicine, 2022)
Abstract. Introduction:. Uterine cervix tumors have an invasive nature, with the capacity to proliferate to surrounding organs such as the vagina, bladder, and rectum, as well as the capacity for dissemination and involvement of structures distant from its place of origin. According to the International Federation of Gynecology and Obstetrics, patients with stages IB I, IB I microscopic (small dimension <4 cm) are indicated for radiotherapy or adjuvant chemoradiotherapy with cisplatin (40 mg/m2). However, cisplatin has side effects such as hematological implications (anemia, neutropenia, and thrombocytopenia), gastrointestinal disorders (nausea, vomiting, diarrhea, constipation), and fatigue. Zingiber officinale contains bioactive compounds that act on pregnancy and postoperative nausea, chemotherapy-induced nausea and vomiting, and also in the management of fatigue, myalgia, and insomnia. This study aimed to evaluate the effects of ginger on chemotherapy-induced nausea and vomiting in patients with cervical cancer undergoing treatment with cisplatin and radiotherapy. Methods and analyses:. A randomized intervention clinical and controlled trial with a triple-blind design is described, comparing the effects of institutional antiemetic therapy alone, as well as in combination with 2 different ginger concentrations. Ethics and dissemination:. Due to the nature of the study, we obtained approval from the Division Ethics Committee of Liga Contra o Câncer. All participants signed an informed consent form prior to randomization. The results of this study will be published in peer-reviewed journals. The data collected will also be available in a public repository of data. Trial registration number:. This study is registered in the Brazilian Registry of Clinical Trials under number RBR-47yx6p9. This study was approved by the Division Ethics Committee of Liga Contra o Câncer under CAAE 40602320.0.0000.5293.